1993
DOI: 10.1139/h93-029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ageing on the Motor Unit: A Brief Review

Abstract: This review briefly summarizes the current state of knowledge regarding age related changes in skeletal muscle, followed by a more in-depth review of ageing effects on animal and human motor units (MUs). Ageing in humans is generally associated with reductions in muscle mass (atrophy), leading to reduced voluntary and electrically evoked contractile strength by the 7th decade for most muscle groups studied. As well, contraction and one-half relaxation times are typically prolonged in muscles of the elderly. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
190
0
12

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(212 citation statements)
references
References 102 publications
10
190
0
12
Order By: Relevance
“…The high frequency of type II fibres in this subject may be related to a special usage of the palate muscles or be a consequence of an ageing process. Previous morphological and electrophysiological investigations have reported that a shift in fibre type proportions occurs during ageing, probably due to degeneration of motor neurons, both in limb (Gollnick et al 1972 ;Larsson et al 1978 ;Aniansson, 1981 ;Larsson, 1983 ;Doherty et al 1993 ;Larsson & Ansved, 1995 ;Trappe et al 1995) and masticatory (Monemi et al 1998) muscles. In limb muscles the atrophy and fibre loss preferentially affect the fast type II fibre population and particularly the type IIB fibres, whereas in one of the human jaw muscles, masseter, the muscle fibre degeneration preferentially affects type I fibres.…”
Section: Fibre Type Compositionmentioning
confidence: 95%
“…The high frequency of type II fibres in this subject may be related to a special usage of the palate muscles or be a consequence of an ageing process. Previous morphological and electrophysiological investigations have reported that a shift in fibre type proportions occurs during ageing, probably due to degeneration of motor neurons, both in limb (Gollnick et al 1972 ;Larsson et al 1978 ;Aniansson, 1981 ;Larsson, 1983 ;Doherty et al 1993 ;Larsson & Ansved, 1995 ;Trappe et al 1995) and masticatory (Monemi et al 1998) muscles. In limb muscles the atrophy and fibre loss preferentially affect the fast type II fibre population and particularly the type IIB fibres, whereas in one of the human jaw muscles, masseter, the muscle fibre degeneration preferentially affects type I fibres.…”
Section: Fibre Type Compositionmentioning
confidence: 95%
“…Analyses from human muscle biopsy samples have consistently demonstrated that type II fibers are more susceptible to aging-related atrophy when compared to type I fibers [3,50]. Doherty [51] reported that the loss of type II fiber area was 20-50%, whereas type I area loss was much less (1-25%).…”
Section: Type II Muscle Fibers and Agingmentioning
confidence: 99%
“…(21) It is well established that the human aging process is associated with a signiicant decline in neuromuscular function and performance. (22)(23)(24) Characteristic of this decline is the inevitable reduction in skeletal muscle mass and associated loss of strength, so-called sarcopenia, that occurs even in the absence of disease speciically affecting the neuromuscular system. Strength decline in upper and lower limb muscles is typically 20-40% by the 7 th decade and greater in older adults.…”
Section: Indones Biomed J 2015; 7(2): 73-86mentioning
confidence: 99%